Gain scheduling PID control with pitch moment rejection for pneumatically actuated active suspension - Ahmad, Fauzi (2009)
This study deals with the use of pneumatically actuated active suspension in canceling out the effects of weight transfer to the vehicle dynamics performance in longitudinal direction. The main content of this study is the development of a full vehicle model, which consists of ride, handling and tire subsystems as to study the vehicle dynamics behavior in longitudinal direction. The full vehicle model is then validated experimentally using an instrumented experimental vehicle based on the driver input from brake and throttle pedals. Two types of vehicle dynamics tests are performed for the purpose of model validation namely sudden braking test and sudden acceleration test. The results of model validation show that the behaviors of the model closely follow the behaviors of a real vehicle with acceptable error. An active suspension control system is then developed on the validated full vehicle model to reduce unwanted vehicle motions during braking and throttling maneuvers such as body pitch angle, body pitch rate, vertical displacement and vertical acceleration of the vehicle body. A proportional-integral-derivative (PID) scheme integrate with pitch moment rejection loop is proposed to control the system. In presented scheme the result verifies improved performance of the proposed control structure during braking and throttling maneuvers compared to the passive vehicle system. It is also noted that the additional pitch moment rejection loop is able to further improve the performance of the PID controller for the system. It is well-known that conventional PID scheme is not robust for controlling the system with unknown disturbances. To improve the performance of PID scheme, a gain scheduling proportional-integral-derivative (GSPID) control with pitch moment rejection loop is then proposed of the active suspension system. The results of the study show that the proposed control structure is able to significantly improve the dynamic performance of the vehicle during sudden braking and sudden acceleration maneuvers compared to conventional PID and the passive vehicle system under various conditions. The effectiveness of the proposed control algorithm on a road test using instrumented experimental vehicle is also observed. Finally, potential benefits in the use of this control are investigated. The result of the study demonstrates the potential benefits of the gain scheduling PID controller in controlling the active suspension.